Analisis Pengelolaan Pengaduan Aspirasi Masyarakat Daerah Oleh DPD RI - Noval Rahman; Izzatusholekha Izzatusholekha (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
Public complaints are an important element in public services to determine public satisfaction with the implementation of public services. The Regional Representative Council of the Republic of Indonesia is an institution that represents regional voices and the interests of a region at the central level, as an institution representing regions the DPD RI is required to listen to aspirations and complaints submitted by regional communities. The aim of this research is to determine the management of complaints from regional community aspirations by the DPD RI. This research uses theory from Gorton (2005). The indicators used in this research are Quality Improvement, Openness to receive complaints, commitment, accessibility, responsiveness, transparency and responsibility, personal in nature. This research method uses qualitative descriptive techniques by collecting data from interviews, observation and documentation. The results of this research show that the principle of improving quality in the implementation of handling complaints from the public has been equipped with adequate facilities/infrastructure. On the principle Openness in accepting complaints means that DPD RI accepts all types of complaints from the public. On the principle commitment is that DPD RI is committed to every aspiration & complaint from the community. On the principle accessibility DPD RI provides access to the public to submit complaints through websites, applications, social media and by coming directly to the office. Responsiveness means that DPD RI does not discriminate in responding to every aspiration & complaint and DPD RI members use a pick-up and drop-off system to listen to aspirations or complaints submitted by the public. On the principle Transparency & Responsibility DPD RI will act transparently & responsibly towards every aspiration & complaint. On the principle Personal Characteristics DPD RI properly safeguards the identity/data of the complainant community.